Clinical impact of number of lymph nodes dissected on postoperative survival in node-negative small cell lung cancer - Takamori, Shinkichi; Komiya, Takefumi; Powell, Emily (Frontiers in Oncology, 2022)
Objectives Small cell lung cancer (SCLC) is a lethal histologic subtype of lung cancer. Although the Commission on Cancer recommends pathological examination of at least 10 lymph nodes dissected (LNDs) for resected early-stage non-small cell lung cancer, its survival benefit of LNDs in patients with early-stage SCLC is unknown. Methods The National Cancer Database was queried for SCLC patients with clinical stage I-II and clinical N0, NX disease per AJCC 7th edition who had undergone lobectomy between 2004 and 2017. Overall survival of SCLC patients by the number of LNDs was compared using Log-rank tests. Univariate and multivariable Cox proportional hazards analyses were performed. Results In total, 688 (42%), 311 (20%), 247 (16%), 196 (12%), 126 (8%), and 36 (2%) of 1,584 patients with early-stage SCLC had ≥10, 7-9, 5-6, 3-4, 1-2, and 0 LNDs, respectively. The sequential improvement in the HRs was no longer evident if the number of LNDs exceeds 4. Patients with ≥3 LNDs (n = 1,422) had a significantly longer overall survival than those with <3 LNDs (n = 162) (hazard ratio for death: 0.76, 95% confidence interval: 0.62–0.94, P = 0.0087). Multivariate analysis revealed that ≥3 LNDs was an independent factor for predicting overall survival (hazard ratio for death: 0.76, 95% confidence interval: 0.61–0.93, P = 0.0083). Conclusions Although we are reluctant to recommend a definitive “optimal number” of LNDs, our findings suggest the prognostic and therapeutic roles for performing ≥3 LNDs in patients with early-stage SCLC who undergo lobectomy.